2013
DOI: 10.1097/ico.0b013e318294b0c0
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties and Validation of the Standard Patient Evaluation of Eye Dryness Questionnaire

Abstract: The SPEED questionnaire was shown to be a repeatable and valid instrument for measurement of dry eye symptoms. The SPEED score also correlated significantly with ocular surface staining and clinical measures of meibomian gland function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
190
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(199 citation statements)
references
References 37 publications
4
190
0
5
Order By: Relevance
“…As reported in a multicenter clinical study, a single TPS treatment resulted in sustained improvement in both signs and symptoms of evaporative DED secondary to MGD at 1 month posttreatment. [16][17][18] Furthermore, observational follow-up studies using different subcohorts of patients from the original multicenter study 18 revealed sustained improvement in both signs (meibomian gland secretion [MGS] scores and, in some cases, tear film breakup time [TBUT]) and symptoms (Ocular Surface Disease Index [OSDI] 19 and Standard Patient Evaluation of Eye Dryness [SPEED] 20,21 questionnaire scores) at 9 22 and 12 months 23 post-TPS treatment when compared with the original 1-month posttreatment data. These TPS treatment results demonstrate an unprecedented duration of treatment benefits for patients suffering from evaporative dry eye secondary to MGD.…”
mentioning
confidence: 99%
“…As reported in a multicenter clinical study, a single TPS treatment resulted in sustained improvement in both signs and symptoms of evaporative DED secondary to MGD at 1 month posttreatment. [16][17][18] Furthermore, observational follow-up studies using different subcohorts of patients from the original multicenter study 18 revealed sustained improvement in both signs (meibomian gland secretion [MGS] scores and, in some cases, tear film breakup time [TBUT]) and symptoms (Ocular Surface Disease Index [OSDI] 19 and Standard Patient Evaluation of Eye Dryness [SPEED] 20,21 questionnaire scores) at 9 22 and 12 months 23 post-TPS treatment when compared with the original 1-month posttreatment data. These TPS treatment results demonstrate an unprecedented duration of treatment benefits for patients suffering from evaporative dry eye secondary to MGD.…”
mentioning
confidence: 99%
“…During the clinical examination, patients were required to complete five of the most common Dry Eye Questionnaires used in the clinical setting: The Ocular-surfacedisease-index (OSDI) [30], Mcmonnies (MQ) [31], the standard patient evaluation of eye dryness (SPEED) [32], the Symptom Assessment in Dry Eye (SANDE) [33] and the Dry Eye Questionnaire (DEQ-5; short version) [34].…”
Section: Symptomatology Assessmentmentioning
confidence: 99%
“…Patient symptom severity scores from the OSDI [17][18][19] and Standard Patient Evaluation of Eye Dryness (SPEED) questionnaires were also reviewed. 20 IVCM images of the palpebral conjunctiva and central cornea were then analyzed by two masked observers.…”
Section: Study Design and Patient Populationmentioning
confidence: 99%